Full Costing Method for Determining Cost of Goods Manufactured and Its Impact on Managerial Pricing Decisions: Evidence from a Grilled Chicken MSME in Indonesia - Octaviano, Dicky; Rahmah, Sufia (Institute of Computer Science (IOCS), 2026)
The culinary MSME sector in Indonesia, particularly grilled chicken businesses, often relies on simplistic cost calculations that overlook fixed overheads, leading to inaccurate cost of goods manufactured (COGM) and suboptimal pricing decisions. This case study applies the full costing method to determine COGM and examines its impact on managerial decisions at Ayam Bakar 3 Putri, a small grilled chicken enterprise in Cipondoh, Tangerang. Using a quantitative case study approach, primary data were collected through documentation, semi-structured interviews, and direct observation during one production cycle (May 2025). The full costing analysis incorporates direct materials, direct labor, variable overheads (e.g., LPG, packaging), and fixed overheads (e.g., maintenance, utilities), yielding a total production cost of Rp 6,929,000 for 416 portions, or Rp 16,656 per unit—higher than the previous simplistic calculation. Findings reveal the prior selling price of Rp 15,000 failed to cover actual costs, risking losses. Consequently, management adjusted the price to Rp 18,500–19,000 (with a 10% profit margin) while implementing operational efficiencies, such as supplier selection and workflow optimization. This adjustment enhances profitability and sustainability amid market competition. The study contributes to the limited literature on full costing in ready-to-eat culinary MSMEs by demonstrating its value for accurate cost visibility and informed pricing in high-competition, daily-operational contexts, unlike prior research focused on manufacturing or raw processing industries